Effects of vegetation and water seasonal variation on habitat use of herons (Aves, Ardeidae) in Tonga Lake (North-East Algeria) - Ahlam CHETTIBI; Ettayib BENSACI; Fateh MIMECHE; Soumia DJAMAI (Studia Universitatis Babeș-Bolyai. Biologia)
The present study was aimed to determine the effect of some environmental factors such as water features and vegetation cover on the distribution and habitat use of herons over different seasons of the bird’s life (breeding, passage and wintering) in Tonga Lake (North East Algeria) from March 2017 to February 2018. We used remote sensing techniques to study the environmental factors variations, we adopted the normalized difference vegetation index (NDVI) to give an estimate of vegetation cover and we used the normalized difference water index (NDWI) to study the water features. In our study, we determine that the abundance and richness of herons species is largely influenced by the water features and vegetation cover. The seasonal variations in the amount of these environmental factors are known to affect the availability of various food items for herons. Eight species of herons were identified during the study period. Pearson’s Correlation Coefficient was used to examine the effect of NDVI and NDWI on the distribution of herons. The results showed that the NDVI was significantly positively correlated with richness and abundance of herons respectively (r=0.728, p<0.05) (r=0.651, p<0.05), whereas the NDWI was significantly negatively correlated with the richness and abundance of herons (r=-0.65, p<0.05) (r=-0.69, p<0.05) respectively.